122 GHz single-chip dual-channel SMD radar sensor with on-chip antennas for distance and angle measurements. Issue 3 (15th June 2015) - Girma, Mekdes G.; Gonser, Markus; Frischen, Andreas; Hasch, Jürgen; Sun, Yaoming; Zwick, Thomas
Abstract : This paper describes the design considerations, integration issues, packaging, and experimental performance of recently developed D-Band dual-channel transceiver with on-chip antennas fabricated in a SiGe-BiCMOS technology. The design comprises a fully integrated transceiver circuit with quasi-monostatic architecture that operates between 114 and 124 GHz. All analog building blocks are controllable via a serial peripheral interface to reduce the number of connections and facilitate the communication between digital processor and analog building blocks. The two electromagnetically coupled patch antennas are placed on the top of the die with 8.6 dBi gain and have a simulated efficiency of 60%. The chip consumes 450 mW and is wire-bonded into an open-lid 5 × 5 mm 2 quad-flat no-leads package. Measurement results for the estimation of range, and azimuth angle in single object situation are presented.